2020
DOI: 10.1097/nmd.0000000000001157
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Nursing Intervention for Patients With Thyroid Cancer on Psychological Distress and Quality of Life

Abstract: The present research aimed to investigate the impact of a psychological nursing intervention on psychological distress and quality of life of thyroid cancer patients. A total of 286 participants were randomly divided into two groups: a control group (n = 143) and an intervention group (n = 143). In addition to routine nursing care, patients in the intervention group were given additional psychological nursing interventions. A reduced edition of the Profile of Mood States was used to evaluate mood disturbance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…At present, the gradual progress in the field of medical technology and nursing has made the development of nursing work more and more concerned about how to improve the physical and mental health of patients. Psychological nursing intervention, along with clinical basic care, gradually becomes key to nursing work (28). The goals of psychological nursing intervention are to improve the patient's care environment, enhance the patient's understanding and grasp of the disease, reduce the patient's fear and tension related to the disease, enhance their self-confidence in the face of cancer, correct their incorrect perception, guide them to respond accurately, and eliminate their anxiety and depression (29).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the gradual progress in the field of medical technology and nursing has made the development of nursing work more and more concerned about how to improve the physical and mental health of patients. Psychological nursing intervention, along with clinical basic care, gradually becomes key to nursing work (28). The goals of psychological nursing intervention are to improve the patient's care environment, enhance the patient's understanding and grasp of the disease, reduce the patient's fear and tension related to the disease, enhance their self-confidence in the face of cancer, correct their incorrect perception, guide them to respond accurately, and eliminate their anxiety and depression (29).…”
Section: Discussionmentioning
confidence: 99%
“…A study [12] conducted on 120 patients with thyroid cancer found that mindfulness-based stress reduction could also signi cantly alleviate the anxiety and depression of patients. Another studies [13,14] using a psychological nursing intervention also found that psychological distress, depression and anxiety could be signi cantly reduced. All of the above studies are generally consistent with the ndings of this paper.…”
Section: Relatively Few Studies Have Been Conducted On Interventions ...mentioning
confidence: 94%
“…At the same time, another study [10] also con rmed that more comprehensive information and correct understanding of the disease were important ways to alleviate the psychological distress of patients with thyroid cancer. Currently, studies have found that measures that can effectively alleviate depression, anxiety, and improve the quality of life of thyroid cancer patients are mainly psychological interventions, including psychological and behavioral interventions [11], mindfulness-based stress reduction [12] and psychological nursing intervention [13,14]. There are few studies that combine knowledge dissemination with psychological interventions to alleviate psychological problems and improve quality of life in thyroid cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Wu et al 10 reported that a 1-year psychological and behavioral intervention could improve functional capacities and QoL, alone with reducing depression and anxiety in patients with DTC who treated with postoperative radioactive iodine. In 2020, Wang et al 11 found that a four-week psychological nursing intervention, including the processes such as improving patient’s care environment, enhancing patient’s understanding of the disease and reducing patient’s fear and tension, could reduce psychological distress and enhance the QoL of thyroid cancer patients. Similarly, He et al 12 reported in 2021 that WeChat app-based perioperative nursing interventions could reduce disease stress and improve positive attitudes and self-management efficacy in patients with thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%